Post-operative monitoring of a strangulated hernia with ischemic bowel as content (Indian Journal of Case Reports, 2024)
One of the most dreaded complications of an inguinal hernia is Strangulated Hernia. Once the diagnosis is established after physical examination and concurrent imaging, the extent and gravity of the pathology need to be assessed intra-operatively. Furthermore, the scope and direction of the surgical intervention must be planned accordingly. This case report describes a case of strangulated hernia causing extensive bowel ischemia which was not subjected to resection and ileostomy due to the possibility of poor post-operative prognosis. Efforts were targeted at preserving the viability of the bowel which was post-operatively evaluated through serial monitoring of the patient’s bowel habits and stool consistency.